Contemporary Control of DG Integrated DVR for Sag, Swell and Harmonic Mitigation - Syed Suraya; P. Sujatha; P. Bharat Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents a novel control strategy to control DG integrated DVR (dynamic voltage restorer) for mitigation voltage quality problems. Power quality is the most concerning areas in power engineering and voltage quality is of prime focus. Voltage sag, voltage swell and harmonics in voltage causes deterioration in quality of voltage delivered to load. A minor disturbance in voltage profile can degrade the performance of load. Dynamic voltage restorer is a quick responsive custom power device for voltage quality improvement. Photovoltaic (PV) system is considered as DG and output voltage of PV system is boosted with a boost converter to support voltage source converter of DVR. DG integrated DVR with novel control strategy for mitigation of voltage sag, swell and voltage harmonic is presented in this paper. The power system model with DG integrated DVR is developed and results are obtained using MATLAB/SIMULINK. Results are discussed during pre and post sag/swell condition with compensation and THD in voltage is maintained within nominal values.